PENGARUH PROMOSI PENJUALAN TERHADAP KEPUTUSAN KONSUMEN MENGINAP DI HOTEL THE PREMIERE PEKANBARU - kurniawan, teuku reza (Sekolah Tinggi Ilmu Ekonomi Riau, 2020)
The purpose of this study is to determine the effect of Sales Promotion on Consumer Decisions to Stay at The Premiere Hotel Pekanbaru. Because sales promotion is one of the main factors supporting the success of a company to market its products, in addition to being seen from how consumers' decisions in determining their choices. The population in this study was 64,738 consumers who stayed at The Premiere Hotel Pekanbaru. Thus the number of samples is 100 consumers. From the results of the analysis formulated a simple linear regression equation with the equation Y = 12.050 + 0.733X. Where, the constant is 12,050, meaning that if the independent variable X (sales promotion) value is 0, then the dependent variable Y (consumer's decision) is 12,050. The variable regression coefficient X (sales promotion) of 0.733 means that if the sales promotion has increased by 1 point, then the consumer's decision will also increase by 0.733. Positive coefficient means that there is a positive relationship between sales promotions with consumer decisions. The higher the sales promotion, the consumer's decision will increase. The test results of the significant test (t), obtained tcount of 8.885 is greater than t table with a ttable value of 1.984, with a significance level of 0.000 <0.05. Thus it means that the sales promotion variable (X) significantly influences the purchase decision variable (Y). So it can be concluded that the sales promotion has a significant effect on consumer decisions to stay at The Premiere Hotel Pekanbaru. R square values (R2) of 0.446 or 44.6% were obtained. This shows that changes in the value of consumer decisions are influenced by changes in the value of the free variable sales promotion by 44.6% while 55.4% is determined by other variables that are not in this research model.